Evaluación de la temperatura superficial en el puente vehicular Primera de Mayo con Avenida Boyacá de la ciudad de Bogotá. (2022)
Bridges are subjected to temperature loads due to climatic action. However, Colombia lacks its own studies to quantify the design values of temperature loads on bridges. Consequently, in this work the objective is to monitor the surface temperature of a concrete bridge and it is carried out on the vehicular bridge of the First of May with Boyacá Avenue in Bogotá. Monitoring is carried out by measuring temperatures with a thermal camera at dawn and midday, for 15 days in two seasons of the year. Surface temperature data is presented at the top and bottom of the dashboard, providing values for future analysis and model calibration. In addition, a transient thermal balance model is performed using the finite difference method with hourly environmental data. The results are compared with the measurements, and it is concluded that the model can be a tool to reproduce the thermal phenomenon for future analyses